The effects of referential gaze in spoken language comprehension: Human speaker vs. virtual agent listener gaze - Nunnemann, Eva M.; Kreysa, Helene; Knoeferle, Pia (Frontiers in Communication, 2023)
Introduction Four studies addressed effects of human speaker gaze vs. virtual agent listener gaze on eye movements during spoken sentence comprehension. Method Participants saw videos in which a static scene depicting three characters was presented on a screen. Eye movements were recorded as participants listened to German subject-verb-object (SVO) sentences describing an interaction between two of these characters. Participants' task was to verify whether the sentence matched a schematic depiction of the event. Two critical factors were manipulated across all four experiments: (1) whether the human speaker—uttering the sentence—was visible, and (2) whether the agent listener was present. Moreover, in Experiments 2 and 4, the target second noun phrase (NP2) was made inaudible, and in Experiments 3 and 4, the gaze time course of the agent listener was altered: it looked at the NP2 referent about 400 ms before the speaker did. These manipulations served to increase the value of the speaker's and listener's gaze cues for correctly anticipating the NP2 referent. Results Human speaker gaze led to increased fixations of the NP2 referent in all experiments, but primarily after the onset of its mention. Only in Experiment 3 did participants reliably anticipate the NP2 referent, in this case making use of both the human speaker's and the virtual agent listener's gaze. In all other cases, virtual agent listener gaze had no effect on visual anticipation of the NP2 referent, even when it was the exclusive cue. Discussion Such information on the use of gaze cues can refine theoretical models of situated language processing and help to develop virtual agents that act as competent communication partners in conversations with human interlocutors.